Hyperoxalosis Secondary to Intravenous Vitamin C Administration as a Non-Allopathic Treatment for Cancer. Issue 1 (March 2019) - Giffen, Mark A.; McLemore, Jerri L.
Vitamin C (ascorbic acid) has long been known to have antioxidant properties, with associated claims that it can boost the immune system, fight off infection, and help in the treatment of cancer. Similar to many other over-the-counter and herbal medicines, vitamin C can cause potential side effects with significant morbidity and rarely mortality. We discuss a case of an elderly woman with metastatic adenocarcinoma of the lung that was treated with several rounds of allopathic chemotherapy; however, treatment was stopped because of worsening quality of life and disease progression. She was treated with 10 courses of intravenous high-dose vitamin C at a local homeopathic medical center as an alternative treatment method. Five days after the last vitamin C administration, she was admitted to an allopathic hospital due to acute renal failure and oliguria culminating in a myocardial infarct due to underlying atherosclerotic disease. Workup revealed dehydration secondary to poor oral intake and acute renal failure which was clinically concerning for calcium oxalate– induced kidney injury. At the time of autopsy, in addition to her widely metastatic adenocarcinoma and myocardial damage, hyperoxalosis of the kidney with acute kidney injury was present. Hyperoxalosis of the kidney is a documented phenomenon related to administration of intravenous and oral vitamin C at superphysiologic doses as recommended by some natural and homeopathic practitioners and is, therefore, a significant complication of treatment. This case highlights the renal complications of supertherapeutic vitamin C administration and the associated morbidity which can contribute to death.